Apoptosis-Inducing Factor, Protein Expression, and Apoptosis Changes with Glutamine in Podocytes Cells Exposed with Cisplatin - Imam Susilo; Himmayatussorofil Maulida; Lindawati Alimsardjono; Dyah Fauziah; Herinda Pertiwi (Veterinary Medicine International)
Cisplatin is a well-known chemotherapeutic drug. It is one of the most effective anticancer agents and is widely used for the treatment of several types of tumors. However, side effects in normal tissues and organs, such as nephrotoxicity that induces apoptosis in epithelial cells in the kidney, limit the use of cisplatin. Glutamine is a substrate for the synthesis of glutathione as an antioxidant and promotes HSP70 release, protecting cells from apoptosis induced by different stimuli. In the present study, we investigated the protective effect of glutamine on cisplatin nephrotoxicity in the kidney. Mice were divided into three groups such as a group of control (P0), a group of intraperitoneal injection of a single dose cisplatin 20 mg/kg BW at 7th day (P1), and a group of intravenous glutamine injection 100 mg/kg BW at days 1–7 and given an intraperitoneal injection of single dose cisplatin 20 mg/kg BW at 7th day (P2). Measurement of AIF expression and apoptotic cells was carried out by immunohistochemical methods. The number of AIF expressions and apoptotic cells is expressed in the Allred score. AIF expression result is as follows: P0: 3.29 ± 0.79, P1: 5.32 ± 0.68, and P2: 4.49 ± 0.47. Apoptosis result is as follows: P0: 3.04 ± 0.70, P1: 5.26 ± 0.53, and P2: 4.44 ± 0.41. There is a decreased expression of AIF on intravenous glutamine administration, followed by a decrease in apoptosis in the podocyte. In conclusion, glutamine administration might represent the treatment of nephrotoxic-induced cisplatin.